2012
DOI: 10.1261/rna.035410.112
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage and polyadenylation specificity factor 1 (CPSF1) regulates alternative splicing of interleukin 7 receptor (IL7R) exon 6

Abstract: Interleukin 7 receptor, IL7R, is expressed exclusively on cells of the lymphoid lineage, and its expression is crucial for the development and maintenance of T cells. Alternative splicing of IL7R exon 6 results in membrane-bound (exon 6 included) and soluble (exon 6 skipped) IL7R isoforms. Interestingly, the inclusion of exon 6 is affected by a single-nucleotide polymorphism associated with the risk of developing multiple sclerosis. Given the potential association of exon 6 inclusion with multiple sclerosis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 61 publications
5
56
0
Order By: Relevance
“…5). This result is consistent with exon 6 skipping being augmented by two insults: strengthening of a weak silencer by the risk allele of rs6897932 (Evsyukova et al, 2013; Gregory et al, 2007) and reduced expression of the activator DDX39B. Collectively, our genetic and functional studies indicate that carriers of both IL7R and DDX39B risk alleles are at highest risk of developing MS, very likely due to increased expression of sIL7R.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…5). This result is consistent with exon 6 skipping being augmented by two insults: strengthening of a weak silencer by the risk allele of rs6897932 (Evsyukova et al, 2013; Gregory et al, 2007) and reduced expression of the activator DDX39B. Collectively, our genetic and functional studies indicate that carriers of both IL7R and DDX39B risk alleles are at highest risk of developing MS, very likely due to increased expression of sIL7R.…”
Section: Resultssupporting
confidence: 85%
“…Using different sets of IL7R exon 6 RNAs and HeLa nuclear extracts we identified a total of 89 candidate trans -factors (Evsyukova et al, 2013). Importantly, we showed that both HeLa and Jurkat T cells recapitulate the SNP rs6897932- and ESE2-dependent changes in IL7R exon 6 splicing (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations